Synthesis and characterization of the novel BiVO 4/CeO 2 nanocomposites - Saranyoo Chaiwichian (2018)
Novel BiVO 4/CeO 2 nanocomposites were synthesized by the hydrothermal method combined with the homogeneous precipitation method. The mole ratios of BiVO 4:CeO 2 were 0.4:0.6, 0.5:0.5, and 0.6:0.4. The obtained BiVO 4/CeO 2 nanocomposites were characterized by X-ray diffraction (XRD) for phase composition and crystallinity. Particle sizes, morphology and elemental composition of BiVO 4/CeO 2 nanocomposites were examined by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy (EDS). The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on all samples. UV-vis diffuse reflectance spectra (UV-vis DRS) were used to identify the absorption range and band gap energy of the composite catalysts. The results indicated that BiVO 4/CeO 2 samples retained monoclinic scheelite and fluorite structures. The morphologies of nanocomposite samples consisted of rod-like, plate-like and spheroidal shapes. Specific surface area (SSABET) of the novel synthesized catalysts drastically increased from 38-62 m 2/g whereas an average BET-equivalent particle diameter (dBET) significantly decreased from 30-12 nm, upon increasing the amount of CeO 2 in the BiVO 4/CeO 2 composite. The absorption spectra of all nanocomposite samples were shifted to the visible region, suggesting the potential application of this novel composite as an active visible-light driven photocatalyst.